Yoga Nidra as Complementary Therapy for Quality of Life: A Narrative Review - Vishwakarma, Mayank; Tripathi, J S (International Research Journal of Ayurveda & Yoga, 2025)
Background: Yoga Nidra, a guided meditative practice rooted in the yogic tradition, is an essential component of yoga that enhances both psychological and physical well-being. This article offers an extensive review of the scientific literature on Yoga Nidra. Materials and Methods: We searched for citations using the keywords “Yoga Nidra and Quality of Life” across various online databases, such as PubMed, PubMed Central, Google Scholar, and the Cochrane Library, covering the years 2012–2025. The search yielded 3080 references. We focused on experimental studies, case studies, and case series published in English that explored the impact of Yoga Nidra on psychological and physical well-being. Results: Yoga Nidra effectively reduced anxiety, depression, and stress across various populations, including women with menstrual disorders, cancer patients, and healthcare professionals, thereby enhancing their psychological well being. This review synthesizes the findings, discusses their mechanisms, and highlights their clinical implications. Conclusion: The evidence supports Yoga Nidra as a holistic, non-invasive practice that improves sleep, cardiac function, and mental health by enhancing parasympathetic activity. Effective treatment across diverse populations reduces anxiety, depression, and stress. Its accessibility and therapeutic potential support its integration into health care. Further research is necessary to establish standardized protocols and to investigate their long-term effects